Expectations of survivors towards disaster nurses in Indonesia: A qualitative study - Herni Susanti; Achir Yani S. Hamid; Sigit Mulyono; Arcellia F. Putri; Yudi A. Chandra (International Journal of Nursing Sciences, 2019)
Objective: This study aims to explore the expectations of survivors towards disaster nurses. Methods: The study used qualitative content analysis. Data were collected in 2017 through three focus group discussions with 21 survivors and in-depth interviews with three community leaders; the respondents had experienced one of the following events: a) an earthquake in Padang 2009, b) a volcanic eruption in Yogyakarta 2010, and c) flooding in Jakarta 2014. Results: Four themes represented survivors’ expectations of what nurses can do in responding to a disaster, including: a) provision of direct nursing care, b) provision of information of health service access, c) provision of resources through cross-sector coordination, and d) disaster preparedness activities for the community. Conclusions: This study suggests the importance of disaster nurses having the competency to update information regarding healthcare access, particularly the utilization of health insurance and providing culturally competent care to the survivors. Disaster nurses are also expected to be able to train the community and families about preparedness-related activities. Besides, these disaster nurses should improve their competency in disaster risk reduction. More broadly, such nurses should have the ability to advocate and coordinate with the local government and other stakeholders regarding access to healthcare services and continuous rapid assessment, so that survivors receive immediate and appropriate treatment. Keywords: Disasters, Focus groups, Health services accessibility, Indonesia, Nurses, Professional competence, Survivors